Potentials and Problems of The Agriculture and Livestock Sector - Christianus Yoseph Ngiso Bhae; Jean Nihana Manalu; Wihelmina Loda (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
The research was conducted with quantitative and qualitative analysis. Quantitative analysis was done by recording the amount of production and land use in each sector owned by each village in two sub-districts. Qualitative analysis was carried out by using questionnaires and recording the problems that existed in each village in these two sub-districts. Jerebuu district consists of 12 villages, namely Dariwali, Naruwolo, Tiworiwu, Watumanu, Nenowea, Naruwolo I, Naruwolo II, Dariwali I, Niowela, Tiworiwu I, Tiworiwu II, and Batajawa. Agricultural development aims to increase production to stabilize food.